2021
DOI: 10.1101/2021.02.02.429480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of immunogenicity and protective efficacy of ZyCoV-D DNA vaccine candidates in Rhesus macaques against SARS-CoV-2 infection

Abstract: Vaccines remains the key protective measure to achieve herd immunity to control the disease burden and stop COVID-19 pandemic. We have developed and assessed the immunogenicity and protective efficacy of two formulations (1mg and 2mg) of ZyCoV-D (a plasmid DNA based vaccine candidates) administered through Needle Free Injection System (NFIS) and syringe-needle (intradermal) in rhesus macaques with three dose vaccine regimens. The vaccine candidate 2mg dose administered using Needle Free Injection System (NFIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…The DNA plasmid construct was transformed into Escherichia coli DH5‐alpha TM chemically competent cells. 131 , 132 , 137 ZyCoV‐D is the first Covid‐19 vaccine approved for young adults older than 12 years. 125 The phase 1 part of the phase 1/2 clinical trial found the DNA vaccine candidate safe and tolerable.…”
Section: Promising Covid‐19 Vaccine Candidatesmentioning
confidence: 99%
“…The DNA plasmid construct was transformed into Escherichia coli DH5‐alpha TM chemically competent cells. 131 , 132 , 137 ZyCoV‐D is the first Covid‐19 vaccine approved for young adults older than 12 years. 125 The phase 1 part of the phase 1/2 clinical trial found the DNA vaccine candidate safe and tolerable.…”
Section: Promising Covid‐19 Vaccine Candidatesmentioning
confidence: 99%
“…It exhibited an efficient immune response. Abdala (CIGB 66), a protein-based vaccine, is under phase 3 clinical trial (Yadav et al 2020 ; Ward et al 2020 ). Medicago is an influenza vaccine that is under trial.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…ZyCoV-D, in preclinical studies induced neutralizing antibody response along with Th-1 response and elevated interferon-γ levels. Yadav et al evaluated the immunogenicity and protective efficacy of ZyCoV-D formulations at varying doses in Rhesus macaques [ 102 ]. The vaccine at 2 mg dose successfully induced S1 specific IgG and neutralizing antibody titers, which increased gradually on the viral challenge for up to 2 weeks protecting from lung disease.…”
Section: Vaccines Approved For Public Usementioning
confidence: 99%